Peran komunikasi interpersonal dalam pelayanan kesehatan gigi (The role of interpersonal communication integrated with medical dental care) - Hanindio Soelarso; Roesanto Heru Soebekti; Achmad Mufid (Dental Journal (Majalah Kedokteran Gigi), 2005)
This article is a literature study, concerning the interpersonal communication role in conjunction with technical dental and oral health care conducted by the dentists towards the patient individually. In addition, interpersonal communication means to be synergic communication among dentist and the patient. In relation with the verbal or non verbal dental care process, the effectiveness of interpersonal communication is identified through the perception of the messages and it’s translated by recipient perception, and it will be the same meaning as the messager’s perception. In this case, the dentist and the patient will be capable to send or accept mutual messages as messanger and message recipient. In conclusion, in the dental and oral medical care on the procedure point of view, the similar perception determines very much the successfulness of the wholedental and oral health care process toward diagnosis, determination therapy plan, treatment and post treatment process.